Pengembangan Aplikasi Informasi Wisata Berbasis Web pada Dinas Pemuda, Olahraga, Pariwisata, dan Kebudayaan Kabupaten Tanah Bumbu - Fikri, Muhamad; Purbiyanto, Eko; Assaury, Akhmad Sufyan (Politeknik Harapan Bangsa Surakarta, 2025)
The Department of Culture, Youth, Sports and Tourism as one of the regional apparatus, namely assist Regional Heads in carrying out the preparation and implementation of regional policies in in the fields of youth, sports and tourism, as also mandated in the Law Number 23 of 2014 concerning Regional Government, Head of the Culture, Youth, Sports Service and Tourism, in this case the Head of the Department of Culture, Youth, Sports and Tourism Tanah Bumbu Regency is responsible for the main duties and functions of the department. The purpose of This system was created to utilize digital media to introduce and facilitate tourists to find out information about tourist destinations in the Tanah Bumbu area. Method This web-based tourism information system application in Tanah Bumbu Regency uses rapid application development (RAD) whose goal is to meet user expectations by relatively short time and produces better system quality. This system uses System Development Live Cycle (SDLC) method in the system and language development process PHP programming and using MySQL database. It is hoped that this system will make things easier the public gets faster and easier access to information and to increase the number of tourists visiting. However, this system must be updated regularly according to needs and changes in the work environment. Keywords: Tourist Information Application; Tourist; RAD; MySQL; SDLC